KEBIJAKAN EKONOMI SULTAN AGENG TIRTAYASA DAN PEMBANGUNAN INFRASTRUKTUR PADA MASA PEMERINTAHANNYA - Haki, Ubay; Prahastiwi, Eka Danik (LP2M Universitas Bina Bangsa, 2025)
In this research article, the approach used is a historical approach, which examines various aspects related to history, such as place, time, background, and historical figures. Additionally, this study explores the phenomena that occurred in the past. To strengthen the existing historical theory, an economic approach is also applied in the analysis. The data analysis technique used is descriptive-analytic, where the issues are presented through in-depth analysis, providing an explanation of the role of Sultan Ageng Tirtayasa in the development of the Sultanate of Banten during the period of 1651–1682 CE. The research findings show that the economic condition during Sultan Ageng Tirtayasa's reign was stable and prosperous. The economic policies implemented by Sultan Ageng Tirtayasa made significant contributions to the stability of the economy and the advancement of development in the Sultanate of Banten. These beneficial policies had a positive impact on the development of infrastructure and the economy in the region.